Pengembangan Model Perkuliahan PAKDE (Presentasi, Audiensi, Konfirmasi, Diskusi Dan Evaluasi) berbasis Pendekatan Saintifik - Badrul Wajdi (Universitas Hamzanwadi, 2022)
This study aims to determine: 1) Knowing the characteristics of the product development model of PAKDE lecture based on a scientific approach; 2) Knowing the effectiveness of the application of the PAKDE lecture model based on a scientific approach in improving student learning achievement; and 3) Knowing the effectiveness of the application of the PAKDE lecture model based on a scientific approach in improving the scientific attitude of students. The procedure in this study adapts the development of a 4-D model device developed by Thiagarajan. Field trials using the Wave class with a pretest posttest control group design. Data collection techniques used validation sheets for feasibility data, observation sheets for implementation data, and multiple choice tests for learning achievement data in the cognitive domain of students and questionnaires for data on students' scientific attitudes. The data analysis technique used descriptive statistics to determine the characteristics of the PAKDE lecture model based on a scientific approach, the n-gain score test to determine the increase in learning achievement and the t test to determine the difference in average cognitive learning achievement. The results showed that: 1) The characteristics of the PAKDE lecture model based on the scientific approach that was developed were concluded to be very good; 2) The application of the PAKDE lecture model based on a scientific approach is effective in improving student learning achievement; 3) The application of the PAKDE lecture model based on a scientific approach is effective in improving the scientific attitude of students.